POTENSI, KENDALA, DAN HARAPAN PETANI TERHADAP SUBAK ANGGABAYA SEBAGAI AGROWISATA - Juniasa, I Dewa Nyoman; Umbas, Ronald; Sugiantiningsih, Anak Agung Putu; Merta, I Nengah; Yunita, I Made; Mertaningrum, Ni Luh Putu Erma (Universitas Pendidikan Nasional, 2022)
This research was conducted to find out the potential, constraints and expectations of farmers in Anggabaya Subak as a sustainable subak to become agro-tourism. The research method used is descriptive qualitative. A qualitative approach was used to analyze the data from a survey of the community in Anggabaya Village. From the interview, it can be seen that Anggabaya subak has the potential to be developed into an agro-tourism. The obstacles faced are infrastructure problems such as roads, parking, toilets, and other supporting facilities that are not sufficient. The hope is to be able to open new job opportunities for local communities and be able to increase added value for farmers in Anggabaya subak. All efforts to make Subak Anggabaya an agro-tourism must be carried out by preserving nature and culture. Water sources, rice fields, farmers, subak temples, and autonomous properties both inside and outside must remain but must also be present.